Investigation of acute toxicity and hepaprotective effect of extracts of Nepeta cataria L. - Grytsyk, A.; Struk, O.; Stasiv, T. (Actual Problems of Medicine and Pharmacy, 2021)
The results of preliminary phytochemical studies indicate that the herb Nepeta cataria L. is a promising source of valuable biologically active substances. The aim of the work was to study the acute toxicity and hepatoprotective effect of dry extracts of the herb Nepeta cataria L. Materials and methods: we studied the hepatoprotective activity of Nepeta cataria L. extracts on a screening model of acute tetrachloromethane hepatitis [8] according to the method of A.V. Stefanov. The hepatoprotector of the domestic production of the Silibor tablet was used as a reference drug (Stefanov A.V., 2001). Acute toxicity and hepatoprotective effect of dry extracts of the herb Nepeta cataria L. It was found that the extracts of the herb Nepeta cataria L. are practically non-toxic substances when administered intragastrically. It can be concluded that according to the classification of substances according to the toxicity of Sidorov K.K., these phytosubstances from lingonberry leaves can be attributed to the V class of toxicity (low-toxic compounds). The research results indicate that the aqueous-alcoholic extract of the herb Nepeta cataria L. in acute toxic liver damage exhibits hepatoprotective activity.